Eikonal Tomography of the Southern California Plate Boundary Region. Issue 9 (14th September 2019) - Qiu, Hongrui; Lin, Fan‐Chi; Ben‐Zion, Yehuda
Abstract: We use Eikonal tomography to derive phase and group velocities of surface waves for the plate boundary region in Southern California. Seismic noise data in the period range 2 and 20 s recorded in year 2014 by 346 stations with ~1‐ to 30‐km station spacing are analyzed. Rayleigh and Love wave phase travel times are measured using vertical‐vertical and transverse‐transverse noise cross correlations, and group travel times are derived from the phase measurements. Using the Eikonal equation for each location and period, isotropic phase and group velocities and 2‐psi azimuthal anisotropy are determined statistically with measurements from different virtual sources. Starting with the SCEC Community Velocity Model, the observed 2.5‐ to 16‐s isotropic phase and group dispersion curves are jointly inverted on a 0.05° × 0.05° grid to obtain local 1‐D piecewise shear wave velocity ( Vs ) models. Compared to the starting model, the final results have generally lower Vs in the shallow crust (top 3–10 km), particularly in areas such as basins and fault zones. The results also show clear velocity contrasts across the San Andreas, San Jacinto, Elsinore, and Garlock Faults and suggest that the San Andreas Fault southeast of San Gorgonio Pass is dipping to the northeast. Investigation of the nonuniqueness of the 1‐D Vs inversion suggests that imaging the top 3‐km Vs structure requires either shorter period (≤2 s) surface wave dispersion measurements or other types of data set such as Rayleigh wave ellipticity. Key Points: Reliable surface wave phase and group dispersion curves for 2.5–16 s are extracted from ambient noise cross correlations Eikonal tomography yields robust isotropic phase and group velocities using an irregular seismic network in Southern California Joint inversion of phase and group velocities significantly improves the velocity structure in the top 3–20 km, particularly near faults